Financial services design via conjoint analysis - Muñoz C., Juan Pablo (Estudios de Administración, 1994)
The article describes the design of a new financial service concept in Chile, by means of conjoint analysis. The concept was named "personal banking" and consists in the offering of highly personalized bank services, oriented to the high-income market segment, so that customers can satisfy all their financial needs without visiting a bank branch. The implicit assumption is that the higher volume of operations of this market segment justifies the offering of a prime service. At the same time, this service may generate a higher customer loyalty, concentrating personal and business bank transactions in the same bank. The results of the research, which was performed in a high-income customer sample segmented by activity: top executives, self-employed professionals and entrepreneurs, revealed a high potential for the personal banking concept. The most valued attributes were Telebank and Personal Banker, which mean time saving for the customer.